IMPLEMENTATION OF EMPLOYEE WORK DISCIPLINE IN THE HUMAN RESOURCES DIVISION OF PT PBM SARANA BANDAR NASIONAL PUSAT - Mella Prestyani Dwi Kasari; Muhammad Takrim (Research Trend in Technology and Management, 2025)
The concept behind this study was the importance of work discipline in improving employee performance and productivity, especially in the Human Resources Division of PT PBM Sarana Bandar Nasional Pusat, a subsidiary of PT PELNI. The Aim of this study was to determine the implementation of employee work discipline that affects the work environment. The research method uses qualitative descriptive with data collection techniques through observation, interviews and documentation over a certain period of time. The results of the study showed that the level of employee discipline is still low, as seen from the high number of lateness and absence. Factors causing low discipline include lack of supervision, a suboptimal attendance system, and lack of sanctions. This finding is very necessary for the proposal of a web-based work discipline monitoring system at PT PBM Sarana Bandar Nasional Pusat to improve work discipline in supporting productivity and achieving organizational goals. So that a joint commitment between management and employees is very important to create a disciplined and professional work environment.